Using Ultra-Wide Band to Analyze Soccer Performance through Load Indicators during a Full Season: A Comparison between Starters and Non-Starters - Reche-Soto, Pedro; Rojas-Valverde, Daniel; Bastida-Castillo, Alejandro; Gómez-Carmona, Carlos D.; Rico-González, Markel; Palucci Vieira, Luiz H. [UNESP]; Paolo Ardigò, Luca; Pino-Ortega, José (MDPI, 2022)
The objectives of this study are: (1) to compare match load demands through load indicators between starters and substitutes, and (2) analyze the degree of correlation in the variables analyzed in this investigation. Twenty-two semi-professional soccer players were analyzed during a full season’s 38 official matches. Participants were assigned to two different groups according to their participation in the game: (a) starting-up players (≥90 min played) vs. substitute players (≥45 min played in the second half). Statistical analysis was performed by using Mann–Whitney U test to conduct pairwise comparison and Spearman correlation to demands correlation in each group. Significant differences in both absolute and relative variables in player load (P, p < 0.01; p < 0.01), metabolic power (MP, p < 0.01; p = 0.15), equivalent distance index (EDI, p = 0.87; p < 0.01), dynamic stress load (DSI, p < 0.01; p = 0.977), energy expenditure (EE, p < 0.01; p < 0.01), high metabolic load events (HMLE, p < 0.01; p < 0.01), and high metabolic load distance (HMLD, p < 0.01; p = 0.09). Overall, high direct correlations in the starting-up group in absolute and relative demands of PL, PM, HMLD, EE, and DSL were found, as well as high inverse correlation in the substitute group in all variables, excluding DSL and HMLD. In conclusion, the absolute differences found suggested a different training load management during training sessions.
Keywords: applied sciences; football; global positioning system; load; technology